PEMBELAJARAN MENGANALISIS UNSUR ALUR TEKS CERPEN DENGAN MODEL DISCOVERY LEARNING BERORIENTASI PADA PENINGKATAN KEMAMPUAN BERKOMUNIKASI PESERTA DIDIK KELAS XI SMA PASUNDAN 1 TAHUN PELAJARAN 2022/2023 - Agis Winardi; Titin Nurhayatin; Lili Sadeli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study is motivated by the low ability of students in analyzing the elements of a short story builder focusing on the plot element of the short story. This is due to the lack of variety of educators in choosing teaching methods and model. The selection of varied teaching methods and model can increase motivation and interest in learning. The purpose of this study was to assess the author's ability to plan, implement, and assess learning using the discovery learning model; assess the ability of students using the discovery learning model; assess the effectiveness of the discovery learning model in learning to analyze the plot elements of short story text; and assess the difference in the ability of the experimental class using the discovery learning model with the control class that applied the discussion method. The research approach used is a pseudo-experimental quantitative approach. The research design was pretest-posttest control group design. The data obtained, namely the pretest and posttest results of the experimental and control classes at Pasundan 1 High School Class XI. The results of this study prove that:1) the author is able to plan, implement, and assess learning by obtaining an average of 4 on planning and 3.84 on implementation; 2) the ability of students increases on the pretest average of 48 to 98.50 on the posttest; 3) discovery learning is effectively used in learning to analyze the plot of short story texts, as evidenced by the results of the Mann-Whitney test showing asymp. sig. 0.002; and 4) there are differences in the ability of students in the experimental class and control class, as evidenced by the results of the Wilcoxon test showing asymp. sig. in the experimental and control classes is 0.003. Thus, the discovery learning model is effectively used in learning to analyze the plot elements of short story text.